Which tool for a tennis serve evaluation? A review. (2nd November 2017) - Tubez, F.; Schwartz, C.; Paulus, J.; Croisier, J.-L.; Brüls, O.; Denoël, V.; Forthomme, B.
Abstract: For coaches, the most common and easiest way to analyse the tennis serve is to refer to their own vision. However, human vision is insufficient to observe high-speed motion with great precision. With the improvement of technology, it is now possible to study the gesture from a quantitative point of view. The quantitative evaluation of the tennis serve focuses on the kinematics and kinetics of the player but also on the stroke result, which includes the ball speed and the ball trajectory. This review aims to highlight the current tools available for players, coaches, medical staffs and biomechanical researchers, to evaluate the tennis serve. This overview will provide information to the player's entourage in order to choose the right tools depending on their specific purposes. All of these tools can be applied in performance improvement and injury prevention.